2012
DOI: 10.1002/jssc.201101108
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of carbofuran, carbosulfan, isoprocarb, 3‐hydroxycarbofuran, and 3‐ketocarbofuran by micellar electrokinetic chromatography

Abstract: We developed an analytical method for the detection and quantitation of five pesticides and some of their metabolites - 3-hydroxycarbofuran, 3-ketocarbofuran, carbofuran, carbosulfan, and isoprocarb - using micellar electrokinetic chromatography coupled with a UV-Vis detector. The optimum separation conditions were 20 mM phosphate buffer (pH 8.0) containing 15 mM sodium dodecyl sulfate. The detection wavelength was set at 200 nm and the applied voltage was 12.5 kV. Under these conditions, baseline separation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
(35 reference statements)
0
7
0
1
Order By: Relevance
“…All experiments were performed using an in‐house instrument, similar to that described previously , which consisted of a −20 kV high‐voltage power supply (ES20N‐20W/DAM, Gamma High Voltage Research Inc., Ormond Beach, FL, USA) and UV–Vis detector (SAPPHIRE 600 detector, ECOM, Prague, Czech Republic). Electropherograms were recorded and processed using DataApex Software (DataApex, Prague, Czech Republic).…”
Section: Methodsmentioning
confidence: 99%
“…All experiments were performed using an in‐house instrument, similar to that described previously , which consisted of a −20 kV high‐voltage power supply (ES20N‐20W/DAM, Gamma High Voltage Research Inc., Ormond Beach, FL, USA) and UV–Vis detector (SAPPHIRE 600 detector, ECOM, Prague, Czech Republic). Electropherograms were recorded and processed using DataApex Software (DataApex, Prague, Czech Republic).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the effect of SDS concentration on the separation of analytes, the SDS concentration was varied from 15 to 30 mM in 5 mM phosphate buffer at pH 3.7. The CMC of SDS in water is ~8.2 mM [30]. The positive charged analytes interacted with negative charged SDS micelles to form ion pairs.…”
Section: Effect Of Sds Concentrationmentioning
confidence: 99%
“…2,3 These pesticides are derived from carbamic acid with the introduction of different substituents. 4,5 Studies have shown that exposure to carbamate pesticides can cause endocrine disorders, cancer, deformities, and other serious diseases. 6,7 Isoprocarb (IPC) is one of the most important carbamate pesticides and works by contact and stomach poisoning of pests.…”
Section: Introductionmentioning
confidence: 99%